Finite element models in the problem of calculation of airport paving - Цихановський, В.К.; Коряк, О.С. (Proceedings of National Aviation University (archive), 2006)
Method of solution on strength and stability of airdrome outercoveres with investigation non-homogeneous anisotropic soil half-space are presented. Examples finite element models for solution soil, unsolid and light outercoveres with utilization of effective momental scheme of finite element on base of universal space-shell finite element.